Microtremor based seismic vulnerability assessment of UIN mataram campus II, Lombok - ilham, ilham; Sani, Muhammad Anwar (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
The 2018 Lombok Earthquake caused extensive damage, severely impacting UIN Mataram. This study assesses the seismic vulnerability of the ground at UIN Mataram Campus II using the Horizontal-to-Vertical Spectral Ratio method applied to microtremor data. Measurements were conducted at 27 points with an approximate spacing of 100 meters. Each recording lasted 40 minutes, with a sampling rate of 100 Hz. Data were processed using Geopsy software to extract HVSR curves, with further analysis of reliability and clarity performed using MHVSR-Control, a Python-based GUI. The results reveal that the campus ground is characterized by a low fundamental frequency of 0.60 to 0.66 Hz and a high maximum amplification factor of 5.21 to 22.48, indicating a thick, soft sedimentary layer with high impedance contrast relative to the underlying bedrock. The seismic vulnerability index was extremely high, ranging from 44.5 to 815.08, with the highest values concentrated in the southern part of the campus. These values exceed the thresholds for structural damage, confirming that the UIN Mataram campus II is highly vulnerable to earthquake damage. These findings are critical for campus spatial planning, structural design, and disaster mitigation, supporting national strategies to enhance earthquake resilience.